Housewives’ Opinions and Perceptions about Care Work in Costa Rica - Sandoval-Carvajal , Irma (2022)
The following article presents the main results of a survey for housewives about the unpaid care work they do within their homes. In addition, a characterization of these women’s profile was made from the National Survey of Time Use, both from 2017. Among the main results, it was found that they are women with an average age of 42 years, with a low educational level, a fifth of them do not have social security, and they are women who dedicate to this work about 54 hours a week, compared to the 34 hours other women dedicate per week and well above the 14 hours men dedicate per week to this type of work. 62% of them consider that domestic work at home limits them to achieve economic autonomy, and seven out of ten perceive a low or medium level in their physical and mental well-being, due to the frequency of ailments, of which stress, fatigue, insomnia, and depression prevail.